The intellectual profile of children with autism spectrum disorders may be underestimated: A comparison between two different batteries in an Italian sample. (July 2019) - Giofrè, D.; Provazza, S.; Angione, D.; Cini, A.; Menazza, C.; Oppi, F.; Cornoldi, C.
Abstract: Intelligence measures are typically used in the assessment of children with autism spectrum disorders (ASD), but there is a paucity of research on the implications of such testing. In the present study, we examined children with ASD using two of the most largely adopted instruments, i.e., the WISC-IV, arguably the most utilized scale in the world; and the Leiter-3, a nonverbal scale that also excludes, from the IQ calculation, working memory and processing speed, which are points of weakness in ASD. Results showed that IQ and indices of these two batteries are strongly correlated. However, the WISC-IV IQ might underestimates the potential of children with ASD, particularly in children with a low functioning profile. These hold true for both the full scale IQ and three out of four indices of the WISC-IV, with remarkable implications for both assessment and treatment of these children. Practitioners working with children with ASD should be aware that the battery that they are using might severely affect the estimation of these children's potential.